PERANCANGAN DATABASE ACCESS KODEFIKASI PENYAKIT MENTAL DAN PERILAKU SEBAGAI PEMBELAJARAN MAHASISWA DI STIKES DHARMA LANDBOUW PADANG - Sari, Dian; Maisharoh, Maisharoh; Cholifa, Syadita (Ensiklopedia of Journal, 2024)
Technological developments also have an impact on the world of health, one of which is the implementation of RME (Electronic Medical Records). In the world of education, campuses, especially medical records and health information study programs, are expected to apply learning for this matter. The aim of this research is to obtain the effectiveness of database-based application design for access coding of mental illness and behavior as learning for STIKES Dharma Landbouw Padang students. The type of research used is Research and Development. The population was level III medical records students with a sample of 20. The research was conducted by observation and interviews using descriptive analysis techniques. The research results showed that a database access-based coding application design used Unified Modeling Language (UML) visual modeling, namely use case diagrams, class diagrams and activity diagrams. As well as using Microsoft Excel to create code tabulations, the design is attractive and easy to use. Research results from observations showed that the average coding time was 22.2 seconds with a code accuracy percentage of 100%. The design of a database-based coding application for access to mental and behavioral illnesses for student learning can be said to be efficient and effective when viewed in terms of time and code accuracy. It is hoped that this application can be developed in the laboratory for use in learning so as to support the implementation of RME in Yankes.Keywords : Databases; Codification; Mental; Behavior; Design